Rwanda : Fourth Review Under the Policy Support Instrument-Press Release; Staff Report; and Statement by the Executive Director for Rwanda. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses key issues and policies for the Rwandan economy. Economic growth in Rwanda has been stronger than expected in 2015. However, growth prospects in 2016 appear gloomy. For example, mining exports have been almost halved in recent months due to low price and low demand. The principal tool to tackle the slump in the economy is continued exchange rate flexibility, accompanied by modest tightening of the monetary stance. Also, there are mid-term policies, for example, export diversification, improved revenue mobilization, and better public financial management that can help achieve sustained high and inclusive growth while strengthening resilience.